2018
DOI: 10.1155/2018/5836293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formation Dip on Gas Production from Unconfined Marine Hydrate-Bearing Sediments through Depressurization

Abstract: The effects of geologic conditions and production methods on gas production from hydrate-bearing sediments (HBS) have been widely investigated. The reservoir was usually treated as horizontal distribution, whereas the sloping reservoir was not considered. In fact, most strata have gradients because of the effects of geological structure and diagenesis. In this study, based on currently available geological data from field measurements in Shenhu area of the South China Sea, the effects of formation dip on gas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…Besides the geophysical properties of hydrate reservoirs, the inclination of hydrate formation was another exploitation-affected factor. It is concluded, from the numerical study of Yuan et al regarding the gas production of hydrate-bearing reservoirs in the Shenhu area, SCS, that the increase of dip angle increases the cumulative production of hydrate-released methane, and it might lower the water production by restricting water from the boundary . Chen et al also indicated inclined reservoirs showed higher gas production efficiency and lower water production .…”
Section: Advances On Natural Gas Hydrate Exploitation In the Scsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the geophysical properties of hydrate reservoirs, the inclination of hydrate formation was another exploitation-affected factor. It is concluded, from the numerical study of Yuan et al regarding the gas production of hydrate-bearing reservoirs in the Shenhu area, SCS, that the increase of dip angle increases the cumulative production of hydrate-released methane, and it might lower the water production by restricting water from the boundary . Chen et al also indicated inclined reservoirs showed higher gas production efficiency and lower water production .…”
Section: Advances On Natural Gas Hydrate Exploitation In the Scsmentioning
confidence: 99%
“…They had focused on the effect of formation inclination on the gas production and the simulation results indicated that it was a controlling factor in the horizonal well configuration. 135 Sun et al brought up an idea of the multiple vertical wells system based on the actual hydrate reservoir status in the SCS to develop a hydrate reservoir and simulated the dissociation process. 132 The analysis noted that well spacing had a significant influence on the production performance and a multiple well system could bring great benefits for hydrate exploitation under proper operation conditions.…”
Section: Advances On Natural Gas Hydratementioning
confidence: 99%
See 2 more Smart Citations
“…From the results, when the NGH reservoir size was 1495.2 m × 400 m × 800 m, the horizontal well length was 1495.2 m, the bottom hole producing pressure was 2.76 MPa, and the daily production of the horizontal well was 4.2 × 10 5 m 3 /day, which met the requirement of the industrial gas flow rate (3.0 × 10 5 m 3 /day). But in 2018, Yuan 22 pointed out that exploiting hydrate by horizontal wells can bring about high yield water problems. In 2019, Feng et al 23 also pointed out that horizontal wells are not suitable in formations with high initial saturation and permeability of NGH reservoirs.…”
Section: Introductionmentioning
confidence: 99%